EP252 Para-aortic lymph node involvement revisited in the light of the revised 2018 FIGO staging system for cervical cancer: a retrospective, dual-institutional study. (1st November 2019) - Ayhan, A; Aslan, K; Oz, M; Tohma, YA; Kuscu, E; Meydanli, MM
Abstract : Introduction/Background: This dual-institutional, retrospective study aimed to determine the clinicopathological risk factors for para-aortic lymph node (LN) metastasis among women who underwent radical hysterectomy with systematic pelvic and para-aortic lymphadenectomy for 2009 FIGO stage IB1-IIA2 cervical cancer. Methodology: Institutional cervical cancer databases of two high-volume gynecologic cancer centers in Ankara, Turkey were retrospectively analyzed. Those featured in the study included women with 2009 FIGO stage IB1-IIA2 disease who underwent radical hysterectomy with pelvic and para-aortic lymphadenectomy between January 2006 and December 2018. We analyzed the patient data and investigated all potential predictive factors for para-aortic LN metastasis. Results: A total of 522 women met the inclusion criteria. Pelvic LN metastasis was detected in 190 patients (36.4%); para-aortic LN metastasis in 48 patients (9.2%), isolated para-aortic LN metastasis in 4 (0.8%), and both pelvic and para-aortic LN metastasis in 44 (8.4%) women, respectively. The independent risk factors identified for para-aortic LN involvement included parametrial invasion (odds ratio [OR]: 3.57, 95% confidence interval [CI]: 1.65–7.72; p=0.001), metastasized pelvic LN size >1 cm (OR: 4.51, 95% CI: 1.75–11.64; p=0.002), multiple pelvic LN metastases (OR: 3.83, 95% CI: 1.46–10.01; p=0.006), and common iliac LN metastasis (OR: 2.97, 95% CI: 1.01–8.68; p=0.04). A total of 196 (37.5%) patients exhibited at least one risk factor for para-aortic nodal disease. Conclusion: Parametrial invasion, metastasized pelvic LN size >1 cm, multiple pelvic LN metastases, and common iliac LN metastasis seem to be independent predictors of para-aortic LN involvement. Disclosure: Nothing to disclose.